Women Enrolled in Mining Engineering: Evolution of Female Participation in Mining Engineering in Chile, 1994–2025 - Hurtado-Cruz, J (Elsevier Ltd, 2026)
Chile ranks first globally in copper production. Mining in Chile is an undisputed pillar of the economy, accounting for 10 % of the country’s Gross Domestic Product (GDP) and 11.7 % of exports as of March 2025 (Instituto Nacional de Estadísticas, 2025). This industry is not exempt from major global challenges such as climate change and digital transformation. To meet these goals, the incorporation of women into this traditionally male-dominated field has become a necessity, bringing diversity, innovation, and greater productivity to the sector. This study analyzes the evolution of female participation in the Civil Mining Engineering and Mining Execution Engineering programs at the Universidad de Santiago de Chile (Usach–Ex UTE) over three decades. The methodology involves the analysis of historical databases from the Academic Registry of the Universidad de Santiago de Chile (USACH), the Department of Evaluation, Measurement and Educational Registration (DEMRE), and gender gap data in higher education from the Undersecretariat of Higher Education (SiES). Since 1994, a total of 1164 women have enrolled, representing 21 % of total admissions. Notably, since 2005, female enrollment at this institution has been on the rise, consistently above 20 %, reaching a record 40 % of admitted students in 2025. Mining Engineering is among the disciplines with low female representation within the fields of Science, Technology, Engineering, and Mathematics (STEM). The trend shows that women entering the Department of Mining Engineering (DIMIN-USACH) have begun to occupy an increasingly significant role, with a remarkable rise in their participation, surpassing the national trend. © © 2025. Published by Elsevier Ltd.